Cell therapy in the treatment of bipolar mania in an animal model: a proof of concept study - Bruna M. Ascoli; Rafael Colombo; Luiza P. Géa; Paula B. Terraciano; Sabrina B. Pizzato; Fernanda S. de Oliveira; Elizabeth Cirne-Lima; Flávio Kapczinski; Adriane R. Rosa (Trends in Psychiatry and Psychotherapy, 2017)
Abstract Introduction The rationale of mesenchymal stem cells (MSCs) as a novel therapeutic approach in certain neurodegenerative diseases is based on their ability to promote neurogenesis. Hippocampal atrophy has been related to bipolar disorder (BD) in preclinical, imaging and postmortem studies. Therefore, the development of new strategies to stimulate the neurogenesis process in BD is crucial. Objectives To investigate the behavioral and neurochemical changes induced by transplantation of MSCs in a model of mania-like behavior induced by lisdexamfetamine dimesylate (LDX). Methods Wistar rats (n=65) received one oral daily dose of LDX (10 mg/kg) or saline for 14 days. On the 8th day of treatment, the animals additionally received intrahippocampal saline or MSC (1 µL containing 25,000 cells) or lithium (47.5 mg/kg) as an internal experimental control. Two hours after the last administration, behavioral and neurochemical analyses were performed. Results LDX-treated rats had increased locomotor activity compared to saline-saline rats (p=0.004), and lithium reversed LDX-related hyperactive behavior (p<0.001). In contrast, the administration of MSCs did not change hyperlocomotion, indicating no effects of this treatment on LDX-treated rats (p=0.979). We did not find differences between groups in BDNF levels (p>0.05) in the hippocampus of rats. Conclusion Even though these results suggest that a single intrahippocampal injection of MSCs was not helpful to treat hyperactivity induced by LDX and neither influenced BDNF secretion, we cannot rule out the possible therapeutic effects of MSCs. Further research is required to determine direct effects of LDX on brain structures as well as in other pathophysiological targets related to BD.